Histological and anatomical development of adventitious buds generated from the multiplication of date palm callus Al-Shwathi cultivar grown ex vivo Phoenix dactylifera L.)) (Journal of the College of Basic Education, 2023)
This study was conducted on the date palm Phoenix dactylifera L. cultivar Al Shuwathi, by cultivating the terminal buds of this cultivar in nutrient media supplemented with auxin "naphthalene acetic acid NAA" and cytokinin "isopentyl adenine" for the purpose of knowing the effect of these media in encouraging budding from the primary callus produced outside the living body. The anatomical study showed the existence of a special mechanism for the differentiation of the adventitious buds formed from the primary callus tissue, through the transformation of some cells into meristematic cells in which rapid divisions occur resulting in the formation of meristemoids. mg/l NAA and 3 mg/l 2iP) led to the development of semi-meristemes into meristems characterized by the presence of a clear nucleus with a length of (100) micrometers and a width of (25) micrometers. It is also clear from the study that tracking the development of the implanted tissue leads to either stimulating the formation of independent nodes that differ in their sizes and shapes and do not take a single pattern in their development, or it may lead to the formation of vascular bundles, or the tissue develops to give adventitious buds. Also, the transfer of adventitious shoots from the stimulation medium to the multiplying medium supplemented with (1 mg / L NAA and 4 mg / L 2iP) led to cell divisions in one axis, followed by cell divisions in two axes, which eventually led to divisions and multiplications in multiple directions. It stimulated the emergence of adventitious buds, and the development of these buds was accompanied by the stimulation of the formation of rootstocks, stems and vascular bundles, which in turn developed into complete cotyledons.